Implementasi Metode Pendekatan Design Thinking dalam Perancangan Aplikasi Pembelajaran Matematika Dasar Berbasis Mobile - Ahlis Noor Kholili (Jurnal Teknik Informatika dan Teknologi Informasi, 2024)
The process of learning Basic Mathematics at the elementary school level still faces various challenges, particularly in terms of the lack of engaging teaching media that align with students' characteristics. This study aims to design and develop a mobile-based Basic Mathematics learning application using the Design Thinking approach. This method was chosen for its empathetic, creative, and user-centered nature, which is expected to produce relevant and interactive learning solutions. The research was conducted through five stages of Design Thinking: empathize, define, ideate, prototype, and test. The research subjects consisted of 25 students and 3 teachers at an elementary school. The empathize stage revealed that students struggled to understand basic concepts such as multiplication and division, and showed low interest in conventional learning methods. Based on these findings, a mathematics learning application was developed featuring three main functions: Learn, Practice, and Quiz. Trial results indicated an average post-test score improvement of 18% compared to the pre-test, along with positive responses from students and teachers regarding the application’s interface and functionality. This application not only supports improved learning outcomes but also enhances students’ motivation through visual approaches and gamification. The conclusion of this study demonstrates that the Design Thinking approach is effective when applied to the development of mobile learning applications, offering a significant contribution to improving the quality and experience of learning basic mathematics for elementary school students.